Correlation Between Adiponectin Receptor with Indices of Glucose Homeostasis and Mediators Of Insulin Sensitivity in Type 2 Diabetic Rats Treated With Puguntano (Curanga felterrae Lour.) Leaf Extract - Lindarto, Dharma; Ihsan, Brama; Syafril, Santi; Saragih, Awaluddin (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
ABSTRACT Objective: Adiponectin receptors (AdipoR) regulates metabolism and has anti-inflammatory and insulin-sensitizing effects. We aimed to determine the relationships between AdipoR with parameters of glucose homeostasis (FPG, insulin, and HOMA-IR), and insulin sensitivity (PPAR-γ and p38MAPK) in T2DM rats treated with puguntano (Curanga felterrae Lour.) leaf extract. Methods: T2DM was induced in Wistar rats aged 8–10 weeks and weighing 180–200 g by high-fat diet (HFD) feeding and low-dose streptozotocin (30mg/kg.bw) administration. The rats were then allocated randomly to a treatment group and a control group (n=24 each). The treatment group was orally administered puguntano leaf extract (200 mg/kg.bb) once daily for 10 days. Subsequently, FPG and plasma insulin were measured, and HOMA-IR was calculated. Results: There was significantly difference between treatment group and control group on AdipoR and parameter of glucose homeostasis (FPG, Insulin, HOMA-IR) and insulin sensitivity (PPAR-γ, p38MAPK (all, p<0.01). In both groups, there were no significantly correlations between of AdipoR with all parameter of glucose homeostasis and insulin sensitivity except PPAR-ϒ (p <0.003) across the entire cohort of rats. Conclusion: Our data suggest that puguntano could improve glucose homeostasis, insulin sensitivity and molecular mediators of insulin sensitivity. There were no significantly correlated between improvement of AdipoR with glucose homeostasis and molecular mediators of insulin sensitivity in T2DM.